Analisis Pendapatan Usahatani Jeruk Siam pada Pola Tanam Monokultur di Desa Buahan Kaja Kecamatan Payangan Kabupaten Gianyar (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of Siam Citrus Farming Income under the Monoculture Cropping Pattern in Buahan Kaja Village, Payangan District, Gianyar Regency. The village of Buahan Kaja is one of the villages located in Gianyar Regency. Siamese oranges are the main commodity in this region. This study aims to: 1) analyze the income of Siamese orange farming under a monoculture planting system in Buahan Kaja Village, Payangan District, Gianyar Regency, and 2) identify the challenges faced by Siamese orange farmers under the monoculture planting system in Buahan Kaja Village, Payangan District, Gianyar Regency. The research sample consists of 54 respondents engaged in Siamese orange farming, selected using purposive sampling. The data for this study were obtained through interviews and documentation, then analyzed using both quantitative and qualitative methods. The collected data were processed using formulas for production costs, revenue, and income of Siamese orange farming. The results of this study show that the average income of Siamese orange farming with a monoculture planting pattern in Buahan Kaja Village reaches Rp 39.694.4477,8 per year, with an average cultivated land area of 47.74 ares. The main challenges faced by Siamese orange farmers in Buahan Kaja Village include climate change, pest and disease attacks, and price fluctuations, which significantly impact their farming activities.
Keywords: income; Siamese orange farming